Photoanodic pyramid texturization of n-Ge(100) in HCl solution: unexpected anisotropy in the surface chemistry of etching. Issue 16 (8th April 2019) - Abrenica, Graniel Harne A.; Lebedev, Mikhail V.; Le, Hy; Hajduk, Andreas; Fingerle, Mathias; Mayer, Thomas; de Gendt, Stefan; van Dorp, Dennis H.
Abstract : Ge pyramid texturization has been demonstrated via photoelectrochemical etching in HCl solution. Abstract : The process of electrochemical etching of n-Ge(100) surfaces was studied for aqueous HCl solutions by voltammetry, atomic force and scanning electron microscopy, reflectance measurements and X-ray photoelectron spectroscopy. Under applied potential conditions, unexpected random pyramid texturization was observed for the high HCl concentration range evidenced by the formation of characteristic (111) facets. The morphological changes were accompanied by a photocurrent enhancement and a decreased reflectance. By patterning the pyramids, a high structure density could be achieved. The resulting decrease of the reflectance indicates that the coupling of light into the semiconductor was improved. Integrated electrochemical X-ray photoelectron spectroscopy measurements allowed us to relate surface chlorination to the obtained morphological features. Photoanodic etching schemes are presented to provide insight into these striking results.